Peran Organisasi Kemasyarakatan Islam dalam Pengembangan Mutu Pendidikan Islam di Indonesia - Rahmat, Mamat (Asosiasi Mahasiswa Program Pascasarjana | Universitas Islam Darussalam (UID) | Islamic University of Darussalam | Ciamis | Jawa Barat, 2023)
This study aims to explore the role of Islamic community organizations in developing the quality of Islamic education in Indonesia. This study uses a literature review method, in which the researcher reviews books, journal articles, research reports, and proceedings of relevant scientific forums. The results of the study show that Islamic community organizations in Indonesia have a great influence on national development. In the context of the development of education in Indonesia, Islamic community organizations have played a significant role in advancing education and developing quality education in the country. The role of Islamic community organizations in advancing Islamic education and developing the quality of education has certainly been felt by the community. Community organizations such as Muhammadiyah, Nahdlatul Ulama (NU), Persatuan Islam/Islamic Association (Persis), Persatuan Umat Islam/Islamic Community Association (PUI) and others, are believed to have made a real contribution in advancing educational institutions in Indonesia. These Islamic community organizations together with the community have proven to have played a significant role in developing the quality of education as well as in equitable distribution of education.